Anthropogenic disturbance and mixed-species groups - Frazier, Eric K.; Freeberg, Todd M. (Frontiers in Ecology and Evolution, 2025)
Mixed-species groups (MSGs) are composed of individuals of two or more species with such close associations that they can be regarded as members of the same social group. MSGs are ubiquitous and are often advantageous for the individuals involved, as these groups confer benefits of exploiting food resources and increased predator detection. Individuals often suffer negative impacts from human-caused disturbances to their habitats. Types of anthropogenic disturbance include outright loss of habitat, habitat fragmentation, and noise. Anthropogenic disturbance can negatively impact behaviors such as communication, foraging, and predator detection. Unsurprisingly, anthropogenic disturbance is a key driver in biodiversity changes across the world. Many studies have focused on the impact of anthropogenic disturbance on single species, but comparatively little work has addressed the influence of anthropogenic disturbance on MSGs. Therefore, a framework is needed to explore how anthropogenic disturbance affects the behavior, composition, and function of MSGs. This brief review paper aims to start to craft such a framework to stimulate research into these questions.